The Haunt of Home : A Journey through America's Heartland - Jack, Zachary Michael, 1973- (Book collections on Project MUSE., 2020)
"Blends cultural ethnography and demography with moving personal memoir to consider the ways a region's duende shapes the ethos of a land and its people"--